Bioreducible and acid-labile poly(amido amine)s for efficient gene delivery - Zhou QH (Dove Medical Press, 2012)
Zhi-Qiang Yu,1 Jun-Jie Yan,1 Ye-Zi You,1,* Qing-Hui Zhou2,*1Chinese Academy of Sciences, Key Laboratory of Soft Matter Chemistry, Department of Polymer Science and Engineering, University of Science and Technology of China, Hefei, Anhui, People’s Republic of China; 2Department of Medicine, University of California at Los Angeles, Los Angeles, CA, USA*These authors contributed equally to this workAbstract: Intracellular processes, including endosomal escape and intracellular release, are efficiency-determining steps in achieving successful gene delivery. It has been found that the presence of acid-labile units in polymers can facilitate endosomal escape and that the presence of reducible units in polymers can lead to intracellular release. In this study, poly(amido amine)s with both bioreducible and acid-labile properties were synthesized to improve gene delivery compared with single-responsive carriers. Transfection and cytotoxicity were evaluated in three cell lines. The complexes of DNA with dual-responsive polymers showed higher gene transfection efficiency than single-responsive polymers and polyethylenimine. At the same time, these polymers were tens of times less cytotoxic than polyethylenimine. Therefore, a polymer that is both reducible and acid-labile is a promising material for efficient and biocompatible gene delivery.Keywords: reducible, acid labile, gene delivery, dual-responsive, endosomal escape, intracellular release